2019
DOI: 10.18002/rama.v14i2s.6022
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the temporal structure of world high competition judo combat (2013 a 2017)

Abstract: <div><p>Judo is a sport that is constantly evolving. Rule modifications and changes in tactical strategies have enhanced scoring opportunities and reduced penalties. This study analyzed the evolution of the temporal structure of combat through an assessment of the total match time (TMT), time engaged in combat (CT), time without (TWOG) and with grip (TWG), pause time (PT), the percentage of combat time in <em>tachi-waza</em> and combat in <em>ne-waza</em>, and the frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The analysis of the TU-GS length (seconds) showed no significant differences from WC18 to WC21 (only for men when both sexes were analysed separately). Some studies have found a longer duration of the contest between 2013 and 2017 due to the change in rules [26]. It was also explained by the reduction from 5 m to 4 m of regular time since the length of GS increased by 3.6% despite the reduction of total regular time [26].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the TU-GS length (seconds) showed no significant differences from WC18 to WC21 (only for men when both sexes were analysed separately). Some studies have found a longer duration of the contest between 2013 and 2017 due to the change in rules [26]. It was also explained by the reduction from 5 m to 4 m of regular time since the length of GS increased by 3.6% despite the reduction of total regular time [26].…”
Section: Discussionmentioning
confidence: 99%
“…Player's performance analysis during the game (match analysis that includes stroke position, ball movement, match sequence, and player's substitutions) is covered in detail in: Pereira et al [19], Michael et al [20], Caballero et al [21], Slawson et al [22], Belli et al [23], Gal et al [24]. Some of the authors, such as Tromp and Holmes [25], Monteiro et al [26], Franchini et al [27], Gimenez-Egido et al [12], García-de Alcaraz et al [28] and Ortega-Toro et al [29], attempt to provide a solution for estimating the impact on performance after rule changes, process model analysis by presenting a solution as an example. The approaches to team analysis are discussed in detail by a number of authors.Young et al [30], Ortega et al [31], Travassos et al [32], Korte and Lames [33], Clemente et al [34] and Laporta et al [35] discussed a social network analysis.…”
Section: Sr1: An Overview Of Sport Performance Analysis In Generalmentioning
confidence: 99%
“…In judo combat, the actions carried out during the time interval between the fighters' approach and the establishment of a grip in the judogi (judo uniform) are pivotal for subsequent actions and determining victory [ [1] , [2] , [3] , [4] , [5] ]. Moreover, the approach and gripping phases across various Olympic cycles consume a significant portion of combat time [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…In a sample of 150 international male and female judo matches from 2010, 59.3 % of effort sequences were comprised of time devoted to grip attempts or successful gripping [ 7 ]. In international championships for both male and female judo from 2013 to 2017, non-grip actions accounted for 25 % of the time spent in combat, while gripping actions made up 36 % [ 6 ]. During matches in the 2016 Olympic cycle, the time dedicated to the approach and gripping phases equaled 39.3 % and 39.9 % of the total combat time, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation